The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/20008198.2021.1968597
|View full text |Cite
|
Sign up to set email alerts
|

Profiles in COVID-19: peritraumatic stress symptoms and their relation with death anxiety, anxiety sensitivity, and emotion dysregulation

Abstract: Background The COVID-19 pandemic might be experienced as an ongoing traumatic event and could result in peritraumatic stress symptoms. Evidence implies that individuals’ levels of death anxiety, anxiety sensitivity, and difficulties in emotion regulation may contribute to their peritraumatic stress symptomatology in the aftermath of trauma exposure. Objective The current study aimed to explore these hypotheses in the context of the COVID-19 pandemic. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(68 reference statements)
3
5
0
Order By: Relevance
“…It was also found that there was not a significant relationship between death anxiety and resilience. But Siegel et al (2021) found that significant relations between anxiety sensitivity and death anxiety Another result of the present study was that there was a significant negative relationship between anxiety sensitivity and resilience. Although not a study examining the relationship between anxiety sensitivity and psychological resilience is available in the literature, there are some studies examining the relationship between anxiety and resilience (Açıkgöz, 2019;Bulut, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…It was also found that there was not a significant relationship between death anxiety and resilience. But Siegel et al (2021) found that significant relations between anxiety sensitivity and death anxiety Another result of the present study was that there was a significant negative relationship between anxiety sensitivity and resilience. Although not a study examining the relationship between anxiety sensitivity and psychological resilience is available in the literature, there are some studies examining the relationship between anxiety and resilience (Açıkgöz, 2019;Bulut, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…2 , the current findings confirmed Hypothesis 1, supporting that COVID-19 victimization experiences are negative stimuli that have a significant predictive effect on smartphone addiction. This result is consistent with previous studies reporting that intolerance of uncertainty of COVID-19 correlated positively with Internet addiction [ 11 ], that experiencing occurrence of COVID-19 resulted in trauma and negative psychological symptoms [ 59 61 ], that fear of COVID-19 was found to influence smartphone addiction and mental wellbeing [ 8 ], that trauma was associated mobile phone addiction and with high insecure attachment [ 12 ], that anxiety about COVID-19 infection was the strongest predictor of smartphone addiction, followed by daily use hours [ 9 ], and risk perception of COVID-19 positively impacted internet addiction [ 5 ]. Aligning with those results, the present study further found the significant relationship between the COVID-19 victimization experience and smartphone addiction among university students.…”
Section: Discussionsupporting
confidence: 93%
“…Siegel et al examined the symptoms of stress, emotions, sensitivity, and anxiety during COVID-19 to determine the mental health problems [ 28 ]. COVID-19 anxiety increased among hospital workers, and many of their family members suffered from depression and anxiety.…”
Section: Methodsmentioning
confidence: 99%